Adherence to Mediterranean dietary quality index and risk of breast cancer in adult women: a case-control study - Farhang Djafari; Parivash Ghorbaninejad; Fatemeh Dehghani Firouzabadi; Fatemeh Sheikhhossein; Hossein Shahinfar; Maryam Safabakhsh; Hossein Imani; Sakineh Shab-Bidar (BMC, 2023)
Abstract Background Breast cancer (BC) is the fifth most prevalent cause of cancer-related deaths in Iran. Given that the role of whole-diet on cancer risk is important, this study aimed to assess the association of MedDQI and breast cancer risk. Methods This hospital-based case-control study was performed on 150 women with pathologically confirmed breast cancer within the period of less than 3 months. Controls were 150 apparently healthy that were matched by age. Dietary data was collected using a validated questionnaire. To examine participants' adherence to MedDQI, the MedDQI was created according to foods and nutrients highlighted or minimized in the MedDQI construction. Results After adjusting for possible confounders, participants in the highest quartile of the MedDQI score had 55% lower odds of breast cancer than women in the bottom quartile (OR: 0.45, 95% CI: 0.21, 0.94, P trend: 0.02). Stratified analysis by menopausal status showed such association in postmenopausal women (OR: 0.24, 95% CI: 0.07, 0.8, P trend: 0.055) after controlling for age and energy intake. Conclusion The results showed an inverse association between adherence to the MedDQI and risk of breast cancer among Iranian women. More prospective studies are needed to confirm our results.